Integrating reality counseling with the creative arts as a counselor's professional practice: A review literature - Titing, Herman (Journal of Professional Teacher Education, 2023)
Counselor creativity is one aspect that needs to be strengthened by counselors in providing counseling services. The creativity of this counselor can encourage the emergence of meaningful counseling services and significantly impact changes in counselee behavior. This article explains the integration of reality counseling with the creative arts. This article is a structured and systematic literature review of the development of ideas and reality counseling research related to the creative arts. This article is an analysis of 51 articles published from 2010 to 2020. In addition, three scientific articles directly relate to combining creative arts and reality counseling. A study of these articles found that creative arts can increase the effectiveness of reality counseling with the WDEP (wants, doing, evaluation, planning) system pattern. Creative arts supporting the efficacy of the WDEP system pattern of reality counseling are drawings, puppets, metaphors, and sand trays. The combination of reality counseling by utilizing creative arts such as drawing, puppets, metaphors, and sand trays produces operational guidelines for counselors consisting of four counseling sessions. Integrating creative arts into reality counseling is a form of professionalism for counselors in counseling services. Operating procedures for combining reality counseling with creative arts are discussed in this article. The findings of this study provide recommendations for further research to identify the effectiveness of counseling empirically in overcoming specific problems in counselees.